(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
Fish is an important food stuff and source of protein all over the world. In Bangladesh fisheries sector contributes a lot in case of earning foreign currency and meeting domestic need of animal protein. To meet the domestic need Bangladesh imports fish and fish products from neighboring countries. But it is evident from several studies that fish items in Bangladesh contain formalin which is a highly hazardous and carcinogenic chemical. An attempt was taken to detect the extent of formalin use in fish available in Dhaka city. From five different local markets five species of fishes were collected and presence of formalin was detected using the “formalin detection kit in fish” developed by Bangladesh Council of Scientific and Industrial Research (BCSIR). The study indicates that 70% Rui fish is formalin contaminated and almost 50% of fish samples contain formalin. Key words: Formaldehyde; BCSIR; Formalin detection kit; Carcinogen; Fisheries; Livestock. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8866 SJPS 2011; 4(1): 49-52